If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -9)(x + -9)(x + -9) = 0 Reorder the terms: (-9 + x)(x + -9)(x + -9) = 0 Reorder the terms: (-9 + x)(-9 + x)(x + -9) = 0 Reorder the terms: (-9 + x)(-9 + x)(-9 + x) = 0 Multiply (-9 + x) * (-9 + x) (-9(-9 + x) + x(-9 + x))(-9 + x) = 0 ((-9 * -9 + x * -9) + x(-9 + x))(-9 + x) = 0 ((81 + -9x) + x(-9 + x))(-9 + x) = 0 (81 + -9x + (-9 * x + x * x))(-9 + x) = 0 (81 + -9x + (-9x + x2))(-9 + x) = 0 Combine like terms: -9x + -9x = -18x (81 + -18x + x2)(-9 + x) = 0 Multiply (81 + -18x + x2) * (-9 + x) (81(-9 + x) + -18x * (-9 + x) + x2(-9 + x)) = 0 ((-9 * 81 + x * 81) + -18x * (-9 + x) + x2(-9 + x)) = 0 ((-729 + 81x) + -18x * (-9 + x) + x2(-9 + x)) = 0 (-729 + 81x + (-9 * -18x + x * -18x) + x2(-9 + x)) = 0 (-729 + 81x + (162x + -18x2) + x2(-9 + x)) = 0 (-729 + 81x + 162x + -18x2 + (-9 * x2 + x * x2)) = 0 (-729 + 81x + 162x + -18x2 + (-9x2 + x3)) = 0 Combine like terms: 81x + 162x = 243x (-729 + 243x + -18x2 + -9x2 + x3) = 0 Combine like terms: -18x2 + -9x2 = -27x2 (-729 + 243x + -27x2 + x3) = 0 Solving -729 + 243x + -27x2 + x3 = 0 Solving for variable 'x'. The solution to this equation could not be determined.
| -33=-3-2x | | 8d-3d-5d+3=4d | | (a+3)(a^2+6a+9)= | | 2/3x-3/2=-1/6 | | .10=F(.05)+(1-F)(.124) | | (3a-5)(7a^2-6a-1)= | | .10=Wf(.05)+(1-Wf) | | .3x^2=-3 | | (x+5)(x^3-6x+3)= | | 12b+38=150 | | (x-6)(x^2-5x+2)= | | 21F=-3.870967742 | | F=-3.870967742+20f | | .10=(F(.05)+(1-f))((.6*.14)+(.4*.10)) | | n^2+13n-30=-7 | | 3b+10-5b=-56 | | f(x)5x^3-6x^2-4x-12atx=3 | | 7(x+3)=15x-31 | | 5-(3x/4)2 | | (6a*4a^4)/(2a)^3=27 | | (-x+1)=-2(5-x) | | 15y+5(1-y)=10 | | 10x+30=25x | | 5+4p=32 | | 2x^2-5x+10x=-10 | | 32/7+5/8=115/56 | | 3/2(1)-3 | | 2+7=12 | | 9-6(x+1)=2(x-4)+27 | | 5v=12 | | -4(4n+8)=4 | | 6x=-37.8 |